PEDAGOGICAL AND PSYCHOLOGICAL IMPORTANCE OF MANAGEMENT COMPETENCE - Umbarova Sabohat Hamza qizi (Bright Mind Publishing, 2025)
Leadership competence is manifested by the leader's strategic thinking, decision-making, team management and motivation skills. The concept of emotional intelligence is the ability of a person to understand and manage his own emotions, to show empathy towards the emotions of others, to communicate effectively and to strengthen social relations. The article states that the harmony of these two concepts is important not only in the individual development of the leader, but also in increasing the overall efficiency of the organization. In the modern management system, the processes of strategic thinking and correct decision-making depend not only on the technical knowledge and experience of the leader, but also on his emotional stability. The combination of leadership competence and emotional intelligence is the main requirement for modern leaders, and by studying this process, it is possible to ensure the stable development of the educational institution. The article is extensively covered with the help of these concepts.
Keywords: Leadership competence, strategic thinking, motivation, emotional intelligence, empathy, social attitude, communication, modern leader.